2016
DOI: 10.21859/mej-10367
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress and relationship between Physician and Nurses

Abstract: Background and Aim: Phenomenon of moral distress in critical care environments, have different effects on the quality of care and good communication between members of caring team, especially Physician and nurses could to be effective in prevention of moral distress in nurses through creating desirable ethical atmosphere. This study aimed to determine the relationship between moral distresses with the Physiciannurses relationship in ICUs of the South Khorasan province. Materials and Methods: 215 nurses were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 1 publication
4
16
2
Order By: Relevance
“…However, they did not report any significant relationship between MD and the education level of the participants. 24,25,33 But unlike our study, BSc was the minimum level of education in most studies. Also, the lack of a significant relationship between MD and work experience in the present study could be due to a low mean of the years of work experience of the participants.…”
Section: Discussioncontrasting
confidence: 72%
“…However, they did not report any significant relationship between MD and the education level of the participants. 24,25,33 But unlike our study, BSc was the minimum level of education in most studies. Also, the lack of a significant relationship between MD and work experience in the present study could be due to a low mean of the years of work experience of the participants.…”
Section: Discussioncontrasting
confidence: 72%
“…3 Moral distress can have essential drawbacks such as stress, frustration, job dissatisfaction and leaving the workplace or even the nursing profession. 4 Moreover, it can lead to physical problems outbreak such as diarrhoea, chills, headache and crying. 5 Consequences of moral distress have been indicated in prior studies that participants had stated they did not tend to get any invasive procedures if the patients were suffered from severe and worse illness, had Dementia or persistent vegetative state.…”
Section: Introductionmentioning
confidence: 99%
“…3 Moral distress can have essential drawbacks such as stress, frustration, job dissatisfaction and leaving the workplace or even the nursing profession. 4…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that burnout syndrome, common among OR personnel, is the result of working in stressful settings which in turn can cause anti-social behavior (28)(29)(30). In addition, ethical distress among nurses is indicative of their inability to work in accordance with their code of ethics (31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%